Methanol synthesis via CO2 hydrogenation: analysis and simulation of kinetic performance using typical industrial conditions - Alexander, J Garrett (Kansas State University, 2021)
Due to the substantial increase in anthropogenic carbon dioxide (CO₂) emissions over the past century, multiple technologies are being explored to capture this greenhouse gas and utilize it as a viable feedstock. A promising outlet for CO₂ is hydrogenation to methanol. Methanol is widely used in the chemical industry, primarily in the production of formaldehyde, methyl-tert-butyl-ether, and acetic acid, as well as an alternative to traditional fuels due to its superior combustion properties. In addition, significant research is ongoing to utilize methanol as an energy carrier for use in fuel cells. Significant research has been done to understand the kinetic performance of Cu/ZnO/Al₂O₃ catalyst for methanol synthesis, however, much of this research involves lower pressures (<55 bar) than is used in many industrial methanol synthesis processes (80-120 bar). In addition, the H₂ to CO₂ ratio in the reactor feed that is used in industry is significantly higher than what was used to develop many of the kinetic experiments and associated models found in the literature review. This work explores the development of a methanol synthesis catalyst including a thorough literature review of catalyst properties, deactivation, and kinetic mechanisms. The catalytic performance of Cu/ZnO/Al₂O₃ catalyst was explored using a kinetic model developed in MATLAB. The results highlight the negative effect that CO in the feed has on conversion at high H₂ to CO₂ ratios. Pressure drop across a packed bed reactor using typical industrial conditions was also simulated and determined to be negligible for typical reactor configurations and catalyst properties. The effects of non-ideality on reactor performance were simulated using industrial methanol synthesis conditions. The results show up to a 5 percent increase in CO₂ conversion is predicted when including thermodynamic effects in the reactor simulation. This phenomenon can be explained by the reduction of partial pressure of the products formed via the methanol synthesis reaction and therefore a shift in equilibrium towards methanol production.
Keywords: Methanol synthesis